Habitus and Personal Trust as a Strategy to Drive Community Participation in the Implementation of Government Policy - Wawan Edi Kuswandoro (PERSPEKTIF, 2023)
This article aims to explore the experiences of the people of Kedunggaleng village, Wonoasih District, Probolinggo City, East Java in implementing government policies in the field of sanitation in the "Community-Based Total Sanitation (STBM)" program. The problem is focused on the community's rejection of the STBM program which then results in acceptance and willingness to participate. In order to approach this problem, theoretical references and phenomenological methods are used. Data were collected through field interviews and analyzed qualitatively. This study concludes that first, community participation comes from the closeness of the habitus with the anatomy of government programs; second, habitus influences people's perception of government programs; third, habitus combined with Personal Trust (personal trust) is an important capital of social engineering strategy to mobilize community participation in the implementation of government programs; fourth, Personal Trust is more dominant than institutional trust in the government; fifth, implementation of government programs that are in line with habitus can maintain social capital and community participation.